2016
DOI: 10.1007/s00603-016-1006-0
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of High-Temperature Fracture Propagation in Anthracite and Destruction of Mudstone from Coalfield Using High-Resolution Microfocus X-ray Computed Tomography

Abstract: The coalfield fire is determined by fractures of coal and rock that provide tunnel for gases and heat exchange. To study fracture propagation at high temperatures, high-resolution X-ray computed tomography (CT) was used to scan anthracite and mudstone samples collected from the Qinshui coalfield, Shanxi Province, northern China. The samples were scanned at 100°C intervals as they were subjected to temperatures of up to 500°C. Three-dimensional images were reconstructed by the CT software to analyze changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Furthermore, mudstone strength and slope stability was signi cantly reduced by the drying-wetting cycle (Xu et al, 2018). In recent years, advanced techniques such as SEM and computed tomography (CT) have been used to study microscopic water-induced weakening mechanisms in mudstone, providing a strong basis for researchers to directly observe the mechanical properties of waterweakened rocks (Jiang et al, 2014;Wang et al, 2015;Xiao et al, 2016;Zhang et al, 2012). However, these techniques are not capable of studying the evolution of rock cracks.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, mudstone strength and slope stability was signi cantly reduced by the drying-wetting cycle (Xu et al, 2018). In recent years, advanced techniques such as SEM and computed tomography (CT) have been used to study microscopic water-induced weakening mechanisms in mudstone, providing a strong basis for researchers to directly observe the mechanical properties of waterweakened rocks (Jiang et al, 2014;Wang et al, 2015;Xiao et al, 2016;Zhang et al, 2012). However, these techniques are not capable of studying the evolution of rock cracks.…”
Section: Introductionmentioning
confidence: 99%
“…Porosity evolution pattern of (a) all coal samples, (b) lignite, (c) lean coal, and (d) anthracite at different temperatures. [Panel (a) has been modified with permission from refs . Copyright 2020, Q. Meng et al Authors under Creative Commons Attribution 4.0 International License (CC BY 4.0).…”
Section: Dynamic Evolution Of Microstructure and Macroscopic Properti...mentioning
confidence: 99%
“…Panel (c) has been modified with permission from ref . Copyright 2012, Elsevier, Ltd. Panel (d) has been modified with permission from ref . Copyright 2016, Springer–Verlag, Wien.…”
Section: Dynamic Evolution Of Microstructure and Macroscopic Properti...mentioning
confidence: 99%
See 1 more Smart Citation
“…The crack network, as a key determinant of gas migration, plays a crucial role in the evaluation of coalfield fire [8,9]. It has been reported that the number, width and length of cracks increases with the temperature [10]. Elick et al [11] examined the surface subsidence caused by coalfield fire and the development law of cracks under the high temperature of coal combustion.…”
Section: Introductionmentioning
confidence: 99%